Correlation between the Thickness and Anterior-Posterior Width of the Masseter Muscle in Ultrasonography with the Intermolar Width in Maxilla and Mandible - Ghazizadeh Ahsaie, Mitra; Valizadeh, Solmaz; Safi, Yaser; Behnaz , Mohammad; Arianezhad, S. Marjan; Moosavi, Zakaria; Ranji, Paniz; Kouchak Dezfouli, Negin (Journal of Dental School, 2025)
Objective(s): The interplay between masticatory muscle function and dental arch size holds considerable significance within the discipline of orthodontics. This research endeavored to quantify masseter muscle dimensions via ultrasonography (USG) and subsequently analyze their correlative relationship with dental arch width. Methods: 45 participants were enrolled in this cross sectional study, stratified by gender and age cohorts. Bilateral USG assessments, utilizing a 7.5 MHz linear transducer, were conducted to quantify masseter muscle thickness and anterior-posterior (AP) width during both relaxed and clenched states. Intermolar width was determined through direct measurement with a metal caliper on dental casts of the maxillary and mandibular arches. Independent samples t-tests were employed to analyze mean differences between male and female subjects. The association between masseter muscle dimensions (thickness and width) and intermolar width was evaluated using Spearman’s rank correlation coefficient and Pearson’s correlation coefficient, as appropriate at p<0.05. Results: The study cohort comprised 20 females and 25 males within the age range of 16 to 30 years. Statistically significant sexual dimorphism was observed, with males demonstrating substantially greater masseter muscle thickness and AP width compared to females in both relaxed and clenched states (p < 0.001). Consistent with expectations, males demonstrated statistically significant greater intermolar widths in both the maxilla and mandible (p < 0.001). Across the entire study population, a statistically significant positive correlation was identified between masseter muscle thickness and intermolar width (p < 0.05). Specifically, individuals exhibiting larger masseter muscle dimensions presented with correspondingly increased intermolar widths in both the maxillary and mandibular arches. However, when these variables were stratified by gender or age group, no statistically significant correlations were observed (p > 0.05). Conclusion:USG is validated as a safe and reproducible technique for the objective measurement of masseter muscle thickness.